The Role of Bhabinkamtibmas Through Door To Door System In Preventing Theft With Aggravated Circumstances in North Jakarta Metro Police Jurisdcition - Eric Pattimura (Indonesian Journal of Police Studies, 2021)
Cases of criminal acts of theft with weights that occurred in the jurisdiction of North Jakarta Metro Police have increased for 3 years starting from 2018 to 2020. The reasons behind this weighted theft include economic demands and public awareness that is still lacking in the importance of maintaining environmental safety. This needs to be followed up so that the crime of theft by weight can be minimized. The implementation of Door to Door System activities by Bhabinkamtibmas in the jurisdiction of the North Jakarta Metro Police in preventing criminal acts of theft by weighting based on the results of research and field observations, it was found that the implementation of the Door to Door System was not optimal and the delivery of material was still general and not specific regarding theft with weights so that there are still many people in North Jakarta who are victims of criminal acts of theft with weights. From the management process that has been implemented to optimize door to door system activities in terms of mobilization and supervision, there are no obstacles, but in terms of planning and organization there are still obstacles so that the optimization of the door to door system does not run optimally. The implementation of Door to Door sambang by Bhabinkamtibmas in the jurisdiction of the North Jakarta Metro Police in preventing the crime of theft by weighting is influenced by several factors in accordance with the SWOT analysis theory in door to door system activities in preventing criminal acts of theft by weighting the jurisdiction of the Jakarta Metro Police so that by Knowing these 4 elements, it is hoped that the implementation of the door to door system can run optimally.